GABA shunt mediates thermotolerance in Saccharomyces cerevisiae by reducing reactive oxygen production. Issue 4 (5th April 2013) - Cao, Juxiang; Barbosa, Jose M.; Singh, Narendra K.; Locy, Robert D.
Abstract The GABA shunt pathway involves three enzymes, glutamate decarboxylase (GAD), GABA aminotransferase (GAT) and succinate semialdehyde dehydrogenase (SSADH). These enzymes act in concert to convert glutamate (α‐ketoglutarate) to succinate. Deletion mutations in each of these genes in Saccharomyces cerevisiae resulted in growth defects at 45°C. Double and triple mutation constructs were compared for thermotolerance with the wild‐type and single mutant strains. Although wild‐type and all mutant strains were highly susceptible to brief heat stress at 50°C, a non‐lethal 30 min at 40°C temperature pretreatment induced tolerance of the wild‐type and all of the mutants to 50°C. The mutant strains collectively exhibited similar susceptibility at 45°C to the induced 50°C treatments. Intracellular reactive oxygen intermediate (ROI) accumulation was measured in wild‐type and each of the mutant strains. ROI accumulation in each of the mutants and in various stress conditions was correlated to heat susceptibility of the mutant strains. The addition of ROI scavenger N‐tert‐butyl‐α‐phenylnitrone (PBN) enhanced survival of the mutants and strongly inhibited the accumulation of ROI, but did not have significant effect on the wild‐type. Measurement of intracellular GABA, glutamate and α‐ketoglutarate during lethal heat exposure at 45°C showed higher levels of accumulation of GABA and α‐ketoglutarate in the uga1 and uga2 mutants, while glutamate accumulated at higher level in the gad1 mutant. These results suggest that the GABA shunt pathway plays a crucial role in protecting yeast cells from heat damage by restricting ROI production involving the flux of carbon from α‐ketoglutarate to succinate during heat stress. Copyright © 2013 John Wiley & Sons, Ltd.